Roles and Rationale of Using English on social media - Panday, Nikesh (Ganeshman Darpan, 2023)
Many people utilize social media as one of the instruments in information and communication technology to communicate ideas in regular communications. The current study identified Tribhuvan University students at various levels who used social media to increase their English language skills. Since this study aimed to gather specific information about social media usage in developing English language competency from the perspective of college students, a survey research design was used. The responses’ results demonstrated that social media (SM) platforms play various roles in enhancing EFL learners’ English comprehension. Most respondents fervently concurred that using social media significantly contributes to developing English ability.